2011
DOI: 10.26719/2011.17.6.523
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of smoking among adolescent schoolchildren in Monastir, Tunisia

Abstract: A study in Monastir, Tunisia estimated the prevalence of smoking and analysed the determinants of tobacco use among adolescents aged 10-19 years. An observational cross-sectional study was performed in the 8 colleges and high schools of Monastir city in 2004. The mean age of the 900 respondents was 15.8 (SD 2.2) years and 47.7% were aged under 16 years. The overall prevalence of cigarette use during the past year was 16.0% (30.2% among males and 4.6% among females). The first smoking experience was initiated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
2
17
3
Order By: Relevance
“…It is estimated that by 2030 the mere mortality rate induced by smoking will reach 10 million a year (Guttmacher, Kelly, & Ruiz-Janecko, 2010). Global body of research has shown that the majority of risky behaviors are initiated prior to the age 18 and they mainly include smoking, alcohol consumption and drug abuse (El Mhamdi, Wolfcarius-Khiari, Mhalla, Salem, & Soltani, 2011;Smith & Wessel, 2011). An investigation conducted in America indicated that from among the student subjects within 30 days in advance to the study, 32.8% had texted or sent emails while driving, 38.7% had consumed alcohol and 23.1% had consumed marijuana.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that by 2030 the mere mortality rate induced by smoking will reach 10 million a year (Guttmacher, Kelly, & Ruiz-Janecko, 2010). Global body of research has shown that the majority of risky behaviors are initiated prior to the age 18 and they mainly include smoking, alcohol consumption and drug abuse (El Mhamdi, Wolfcarius-Khiari, Mhalla, Salem, & Soltani, 2011;Smith & Wessel, 2011). An investigation conducted in America indicated that from among the student subjects within 30 days in advance to the study, 32.8% had texted or sent emails while driving, 38.7% had consumed alcohol and 23.1% had consumed marijuana.…”
Section: Introductionmentioning
confidence: 99%
“…Adult smoking prevalence is estimated at 17.3% according to the “BREATHE study” [1]. This rate remains higher among adolescents rather than adults (from 16 to 29.2%) [2,3]. In addition, cultural factors such as parents who smoke, doctors, nurses, and teachers who smoke in the workplace may add to the creation of a pro-smoking environment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends show rising prevalence of tobacco smoking among youth and earlier age of initiation. According to the World Health Organization and other studies, the prevalence of smoking among school-age adolescents was high, especially in developing countries, with estimates ranging from 14% to 29% (El Mhamdi et al, 2011).There are 1.2 billion smokers globally, of which more than 50% are young people. Malaysia alone has about 5 million smokers, 20% of whom are younger than 18 years old (Al-Sadat et al, 2010).…”
Section: Introductionmentioning
confidence: 99%